Research guidebook : a manual for capstone research projects. - Urgena, John Nico A. (Makati City : Diwa Learning Systems, Inc., 2020)
"The Research/Capstone Project is specialized subject for students taking the science, technology, engineering, and mathematics (STEM) strand. There are nine major content area; data collection, data analysis, conclusions, recommendations, and scientific report/paper. This textbook is a great help toward mastering skills, competencies, attitudes, and values that are necessary in knowledge production and nation building through STEM-based research".
Includes bibliography.
English text.
Keywords: Academic writing; Research